Respons Fisiologis Sapi Pedaging terhadap Pengabutan Air Menggunakan Sprinkler Water - Koekoeh Santoso; Aldo Febriano Tarigan; Komariah (Jurnal Ilmu Pertanian Indonesia, 2023)
Indonesia is facing the problem of low productivity of cattle. To increase the productivity of cattle producer, it can actually be done by relocating the cattle to the comfort zone by observing the physiological response. The purpose of this research is to evaluate the effects of misting cattle’s environment by using water sprinkler on the physiological response and the microclimate of the cattle’s shed. The design used was a paired T-test for physiological and microclimate response variables with 5 replications and a completely randomized design to determine the difference between body surface temperatures. The observations were conducted before water misting and after water misting. The results showed that treatment of misting water in the afternoon significantly decreased (P<0.05) the variables of cage temperature, humidity, temperature humidity index, rectal temperature, respiratory rate, and heart rate. Water misting in the afternoon in cattle produced a good effect on all physiological response variables. Keywords: beef cattle, pen microclimate, physiological responses, water sprinkler